Schwann cell stimulation induces functional and structural changes in peripheral nerves. Issue 4 (10th December 2022) - Ciotu, Cosmin I.; Kistner, Katrin; Kaindl, Ulrich; Millesi, Flavia; Weiss, Tamara; Radtke, Christine; Kremer, Andreas; Schmidt, Katy; Fischer, Michael J. M.
Abstract: Signal propagation is the essential function of nerves. Lysophosphatidic acid 18:1 (LPA) allows the selective stimulation of calcium signaling in Schwann cells but not neurons. Here, the time course of slowing and amplitude reduction on compound action potentials due to LPA exposure was observed in myelinated and unmyelinated fibers of the mouse, indicating a clear change of axonal function. Teased nerve fiber imaging showed that Schwann cell activation is also present in axon‐attached Schwann cells in freshly isolated peripheral rat nerves. The LPA receptor 1 was primarily localized at the cell extensions in isolated rat Schwann cells, suggesting a role in cell migration. Structural investigation of rat C‐fibers demonstrated that LPA leads to an evagination of the axons from their Schwann cells. In A‐fibers, the nodes of Ranvier appeared unchanged, but the Schmidt‐Lanterman incisures were shortened and myelination reduced. The latter might increase leak current, reducing the potential spread to the next node of Ranvier and explain the changes in conduction velocity. The observed structural changes provide a plausible explanation for the functional changes in myelinated and unmyelinated axons of peripheral nerves and the reported sensory sensations such as itch and pain. Main Points: Schwann cell stimulation by LPA caused a reduction in axonal conduction. LPA altered structural organization of unmyelinated and myelinated axons.